PEMANFAATAN SISTEM QUESTION ANSWERING DALAM MENINGKATKAN KAPASITAS PENGETUAHUAN KARYAWAN MENGGUNAKAN METODE LOGIKA FUZZY - Adria Adria (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Every new employee who joins a new company always has to go through a process of adapting either to their work or their environment, especially industrial companies that demand their employees, especially those that are in direct contact with the products sold by the company. Even if the employees who join already have a lot of experience, of course they need a learning process when they are in a new place, especially employees who are new or have no experience at all, of course there is a lot that must be learned first, therefore the company needs a system that can handle problems. the problem. The Question and Answering system is a development system from an existing system where many existing systems use the NLP method or the knowledge base method, therefore the system is designed with the fuzzy logic method, so it is expected to provide more precise information to users.